Closed incision management with negative pressure wound therapy. (July 2014) - Dohmen, Pascal M; Misfeld, Martin; Borger, Michael A; Mohr, Friedrich W
<x xml:space="preserve">Abstract</x> Post-sternotomy mediastinitis is the most severe surgical site infection after sternotomy with an incidence between 1–4% related to the patient co-morbidity. This complication will increase morbidity and mortality and may also have an economic impact. There are guidelines to prevent surgical site infections; however, age and co-morbidities increase and therefore it is important to develop new tools to improve wound healing. This manuscript will give an overview of a new concept using negative pressure wound therapy over a closed incision (so-called, closed incision management) after surgery and will include the principles of negative pressure wound therapy and the positively applied mechanical forces as a permutation of Wolff's law. The use and indication of this therapy is supported by experimental studies divided into physiological and biomechanical property studies. Finally, an overview of clinical studies is given based on the evidence rating scale for therapeutic studies.